Species of Reduviidae (Hemiptera: Heteroptera) associated with a canola crop (Brassica napus L. var. oleifera; Brassicales: Brassicaceae) in Passo Fundo, Rio Grande do Sul, Brazil - Luciano de A. Moura (Revista Chilena de Entomología, 2024)
Predatory species of Reduviidae, Harpactorinae (Hemiptera: Heteroptera) collected in a canola experimental crop (Brassica napus L. var. oleifera, hybrid ALHT B4) in Passo Fundo, state of Rio Grande do Sul (28°14’S; 52°24’W), Brazil were recorded. The bugs were collected in 2019 when the crop was blooming and developing siliques. In total, we made 13 collections using entomological net, totaling 13 hours of sampling effort. Three of these species had their prey also recorded. The relative abundance (%) and identity of the reduviids found are as follows: Apiomerus luctuosus Costa Lima, Seabra & Hathaway, 1951 (0.45%), Arilus carinatus (Forster, 1771) (2.73%), Atrachelus cinereus crassicornis (Burmeister, 1835) (89.10%), Cosmoclopius annulosus Stål, 1872 (5.00%), Harpactor tuberculosus Stål, 1872 (0.45%), Isocondylus elongatus (Lepeletier & Serville, 1825) (0.45%), and Repipta flavicans (Amyot & Serville, 1843) (1.82%). The following prey (with the respective reduviid predator) were also recorded in the area: Nezara viridula (Linnaeus, 1758) (Hemiptera: Pentatomidae) by Arilus carinatus; Astylus (Astylus) quadrilineatus (Germar, 1825) (Coleoptera: Melyridae) by Harpactor tuberculosus, and Diabrotica limitata (Sahlberg, 1823) (Chrysomelidae: Galerucinae: Luperini) by Repipta flavicans.